(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2012)
This study determined the Philippine government’s investment in state HEIs from 2005-2010 and their enrolments vis-á-vis the graduation and labor force participation. Findings reveal that SUCs’ budget increased every year with corresponding increase in expense per head, except for SY 2006-2007. Labor demand is low compared to the number of graduates from SUCs. Thus, analyses reveal that the government had a lost investment in tertiary education because the number of enrollees subsidized by the Philippine government decreased by the time they graduated. The number of those who became employed was even low. Recommendations include a strong link among SUCs, businesses, industries and other stakeholders, SUCs to offer student financial loans on priority courses, and influence they way of thinking of people towards entrepreneurship and self- employment.